2021
DOI: 10.22401/anjs.24.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Forged Copy-Move Recognition Using Convolutional Neural Network

Abstract: Due to the extreme robust image editing techniques, digital images are subject to multiple manipulations and decreased costs for digital camera and smart phones. Therefore, image credibility is becoming questionable, specifically when images have strong value, such as news report and insurance claims in a crime court. Therefore, image forensic methods test the integrity of the images by applying various highly technical methods set out in the literature. The present work deals with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In this state, the exploration phase is occurring, and the global jackals hunting action is to select the male (𝑋 π‘šπ‘Žπ‘™π‘’ ) as the leader and the female (𝑋 π‘“π‘’π‘šπ‘Žπ‘™π‘’ ) as the adherent is represented in Eqs. ( 7) and (8),…”
Section: Feature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this state, the exploration phase is occurring, and the global jackals hunting action is to select the male (𝑋 π‘šπ‘Žπ‘™π‘’ ) as the leader and the female (𝑋 π‘“π‘’π‘šπ‘Žπ‘™π‘’ ) as the adherent is represented in Eqs. ( 7) and (8),…”
Section: Feature Selectionmentioning
confidence: 99%
“…This type of forgery is popular because there is a chance that copied portion of an image has the same content, texture and features [7]. There are different traditional techniques for image forgery detection, which mostly include key-points-based and blockbased feature extraction and matching techniques [8]. Deep learning-based techniques are introduced for overcoming these issues of digital image forgery [9].…”
Section: Introductionmentioning
confidence: 99%
“…In block-based methods image is divided in blocks of fixed dimension and further features are extracted corresponding to each block of image. Ayat fadel et al [25] suggested module used the buster net of three neural networks that basically adopted the principle of training by using Convolution Neural Network (CNN) to extract the most important features in the images. The first and second networks are parallel working to detect and identify areas that have been tampered with, and then display them through two masks.…”
Section: Literature Workmentioning
confidence: 99%